Narrow UVB-Emitted YBO3 Phosphor Activated by Bi3+ and Gd3+ Co-Doping - Zhimin Yu; Yang Yang; Jiaming Sun (Nanomaterials, 2023)
Y0.9(GdxBi1−x)0.1BO3 phosphors (x = 0, 0.2, 0.4, 0.6, 0.8, and 1.0, YGB) were obtained via high-temperature solid-state synthesis. Differentiated phases and micro-morphologies were determined by adjusting the synthesis temperature and the activator content of Gd3+ ions, verifying the hexagonal phase with an average size of ~200 nm. Strong photon emissions were revealed under both ultraviolet and visible radiation, and the effectiveness of energy transfer from Bi3+ to Gd3+ ions was confirmed to improve the narrow-band ultraviolet-B (UVB) (6PJ→8S7/2) emission of Gd3+ ions. The optimal emission was obtained from Y0.9Gd0.08Bi0.02BO3 phosphor annealed at 800 °C, for which maximum quantum yields (QYs) can reach 24.75% and 1.33% under 273 nm and 532 nm excitations, respectively. The optimal QY from the Gd3+-Bi3+ co-doped YGB phosphor is 75 times the single Gd3+-doped one, illustrating that these UVB luminescent phosphors based on co-doped YBO3 orthoborates possess bright UVB emissions and good excitability under the excitation of different wavelengths. Efficient photon conversion and intense UVB emissions indicate that the multifunctional Gd3+-Bi3+ co-doped YBO3 orthoborate is a potential candidate for skin treatment.